Turn-Taking Strategies in Animated Discourse: A Case Study of Elemental (2023) Movie - Ayomi, Putu Nur; Winanda, Ni Putu Yulia (Universitas Cokroaminoto Palopo, 2025)
This study aims to identify and analyze the turn-taking mechanisms in the animated movie Elemental (2023). The main focus is on how the characters in the movie apply strategies of taking the turn, holding the turn, and yielding the turn in their dialogues. This research employs a descriptive qualitative approach and applies the theory of turn-taking by Stenström (1994). The data were collected through transcriptions of the film’s dialogue, which were then classified according to types of turn-taking mechanisms. The analysis revealed a total of 76 turn-taking occurrences, with “taking the turn” being the most dominant strategy with total 43 occurrences. These findings indicate that the characters in Elemental tend to hold their speaking turns in order to convey important or emotional information. This study contributes to the field of discourse analysis in the context of animated media, which, although fictional, presents realistic communication interactions.